Gram-scale synthesis of (±)-tylophorine - Masal, Dattatraya P.; Reddy, D. Srinivasa (Synlett, 2025)
We report a practical scalable synthesis of the natural product (+/-)-tylophorine by using an operationally simple protecting-group-free route from readily accessible starting materials. Synthesis of a cyclic N-acetyl diester compound through cyclization, followed by two key steps (decarboxylation and a Clemmensen reduction), provides access to the target molecule.
Keywords: alkaloids; Clemmensen reduction; decarboxylation; gram-scale synthesis; tylophorine